Altered Actin Dynamics in Cell Migration of GNE Mutant Cells - Devi, Shamulailatpam Shreedarshanee; Yadav, Rashmi; Arya, Ranjana (Frontiers in Cell and Developmental Biology, 2021)
Cell migration is an essential cellular process that requires co-ordination of cytoskeletal dynamics, reorganization and signal transduction. The actin cytoskeleton is central in maintaining the cellular structure as well as regulating the mechanisms of cell motility. Glycosylation, in particular, sialylation of cell surface proteins like integrins regulates signal transduction from extracellular matrix to cytoskeletal network. The activation of integrin by extracellular cues lead to recruitment of different focal adhesion complex proteins (Src, FAK, paxillin, etc.) and activates the signal including Rho GTPases for the regulation of actin assembly and disassembly. During cell migration, the assembly and disassembly of actin filament provides the essential force for the cell to move. Abnormal sialylation can lead to actin signaling dysfunction leading to aberrant cell migration, one of the main characteristics of cancer and myopathies. In the present study, we have reported altered F-actin to G-actin ratios in GNE mutated cells. These cells exhibit pathologically relevant mutations of GNE (UDP N-acetylneuraminic 2-epimerase/N-acetylmannosamine kinase), key sialic acid biosynthetic enzyme. It was found that neither GNE affects the actin polymerization nor binds directly to actin. However, mutation in GNE resulted in increased binding of α-actinin to actin filaments. Further, through confocal imaging, GNE was found to be localized in focal adhesion complex along with paxillin. We further elucidated that mutation in GNE resulted in upregulation of RhoA protein and cofilin activity is downregulated which could be rescued with Rhosin and Chlorogenic acid respectively. Lastly, mutant in GNE reduced cell migration as implicated from wound healing assay. Our study indicates that molecules altering Cofilin function could significantly revert the cell migration defect due to GNE mutation in sialic acid deficient cells. We propose cytoskeletal proteins to be alternate drug targets for disorders associated with GNE such as GNE myopathy.